SRF Fusions Other Than With RELA Expand the Molecular Definition of SRF-fused Perivascular Tumors. (December 2020) - Karanian, Marie; Kelsey, Anna; Paindavoine, Sandrine; Duc, Adeline; Vanacker, Helene; Hook, Liz; Weinbreck, Nicolas; Delfour, Christophe; Minard, Veronique; Baillard, Pauline; Blay, Jean-Yves; Pissaloux, Daniel; et al.
Abstract : Pericytic tumors encompass several entities sharing morphologic and immunohistochemical features. A subset of perivascular myoid tumors associated with the SRF-RELA fusion gene was previously described. Herein, we report a series of 13 tumors belonging to this group, in which we have identified new fusion genes by RNA-sequencing, thus expanding the molecular spectrum of this entity. All patients except 1 were children and infants. The tumors, frequently located in the head (n=8), had a mean size of 38 mm (range 10 to 150 mm) and were mostly (n=9) well-circumscribed. Exploration of the follow-up data (ranging from 3 to 68 mo) confirmed the benign behavior of these tumors. These neoplasms presented a spectrum of morphologies, ranging from perivascular patterns to myoid appearance. Tumor cells presented mitotic figures but without marked atypia. Some of these tumors could mimic sarcoma. The immunohistochemical profiles confirmed a pericytic differentiation with the expression of the smooth muscle actin and the h-caldesmon, as well as the frequent positivity for pan-cytokeratin. The molecular analysis identified the expected SRF-RELA fusion gene, in addition to other genetic alterations, all involving SRF fused to CITED1, CITED2, NFKBIE, or NCOA2 . The detection of SRF-NCOA2 fusions in spindle cell rhabdomyosarcoma of the infant has previously been described, representing a risk of misdiagnosis, although the cases reported herein did not express MyoD1. Finally, clustering analyses confirmed that this group of SRF -fused perivascular myoid tumors forms a distinct entity, different from other perivascular tumors, spindle cell rhabdomyosarcomas of the infant, and smooth muscle tumors. Abstract : Supplemental Digital Content is available in the text.